2022
DOI: 10.1038/s41598-022-22469-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lifestyle risk behaviour clustering on cardiovascular disease among UK adults: latent class analysis with distal outcomes

Abstract: Lifestyle risk behaviours such as smoking, physical inactivity, and unhealthy diet account for a considerable disease burden globally. These risk behaviours tend to cluster within an individual, which could have detrimental health effects. In this study, we aimed to examine the clustering effect of lifestyle risk behaviours on cardiovascular disease (CVD) and CVD risk among adults in the United Kingdom (UK). We performed a latent class (LC) analysis with distal outcomes using the UK Biobank baseline (2006–2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
5
9
0
1
Order By: Relevance
“…This finding is consistent with a study in Brazil that showed that clustered risk factors such as obesity, low fruit/vegetable intake, and lack of vigorous or moderate-intensity activities are significantly associated with the risk of CVD diseases [62]. Multiple combined risks are demonstrated in other studies to increase CVD risks [63].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with a study in Brazil that showed that clustered risk factors such as obesity, low fruit/vegetable intake, and lack of vigorous or moderate-intensity activities are significantly associated with the risk of CVD diseases [62]. Multiple combined risks are demonstrated in other studies to increase CVD risks [63].…”
Section: Discussionsupporting
confidence: 91%
“…If the recorded images do represent a fair reflection of what people with HF were doing throughout the day, then they highlight some interesting patterns. For example, excessive screen or sedentary time might highlight people’s preferences (eg, sitting and watching television) [ 30 - 32 ] or could indicate fatigue, a common symptom of HF. Further, the high number of recorded images of eating and drinking could give some indication of what people with HF were eating (eg, foods high in salt) [ 33 ], and the frequency of drinking fluids, which may be an issue for people with HF who are on fluid restriction [ 4 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em apoio a essa hipótese, estudo realizado entre adultos no Reino Unido analisou o efeito simultâneo de comportamentos de risco (fisicamente inativo, baixa ingestão de frutas e vegetais, alta ingestão de álcool) e encontrou um aumento três vezes maior no risco de DCV em relação àqueles que somente consumiram álcool (Tegegne, et al, 2022);…”
Section: Discussionunclassified